2022
DOI: 10.4103/ehp.ehp_11_22
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Perceptions on Academic Entitlement in Graduate Health Professional Students

Abstract: Objective: This descriptive study evaluates faculty perceptions of academic entitlement (AE) in graduate health professional students. Materials and Methods: A cross-sectional descriptive survey design was used. Demographic data and faculty perceptions on the prevalence of AE in physician assistant students using two validated surveys were collected. One survey assessed AE as a unidimensional construct, and the second used a two-factor scale to assess e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…As for responsibility avoidance, it was previously reported that it positively correlates with entitlement, grandiosity, and narcissism, and negatively correlates with self-confidence, personal control, need for cognition, agreeableness, and meticulousness [ 4 ]. Our results on responsibility avoidance are also in parallel with other findings reported by faculty teaching health professions students who showed AE behaviors related to diminished student responsibility to make up their missed work, among other traits [ 24 ]. With such high scores of these AE components perceived by our sample of faculty among their students, counseling students over the importance for looking at their university education from the perspective of a learner rather than a customer, and raising awareness about the importance of responsibility for their personal and professional growth, may be ultimately needed across pharmacy colleges in our region.…”
Section: Discussionsupporting
confidence: 90%
“…As for responsibility avoidance, it was previously reported that it positively correlates with entitlement, grandiosity, and narcissism, and negatively correlates with self-confidence, personal control, need for cognition, agreeableness, and meticulousness [ 4 ]. Our results on responsibility avoidance are also in parallel with other findings reported by faculty teaching health professions students who showed AE behaviors related to diminished student responsibility to make up their missed work, among other traits [ 24 ]. With such high scores of these AE components perceived by our sample of faculty among their students, counseling students over the importance for looking at their university education from the perspective of a learner rather than a customer, and raising awareness about the importance of responsibility for their personal and professional growth, may be ultimately needed across pharmacy colleges in our region.…”
Section: Discussionsupporting
confidence: 90%